A STUDY OF FACTORS INFLUENCING DESERTIFICATION IN INDIA - MONDAL, SUPARNA (International Journal of Multidisciplinary Research and Studies, 2022)
The environment, ecosystem and sustainable development have become the top priorities keeping the conservation, protection and preservation of resources in mind. There are many factors influencing the natural resources and causing exploitation of resources beyond limits. As a result, desertification has become a concern for the world. Global warming, changing climatic conditions, deforestation have a great deal of contribution towards desertification. However, there are differences found at the outset of regional geographic conditions. It is found that developing and developed economies have different factors, which lead to desertification. The present article aims to examine the key factors, which influence the high-level desertification in India. The study analyzes the influence of population explosion, climate change and human impact on desertification in India. The study is unique and significant since India is highly populated country. Agriculture is the backbone of Indian economy. It is imperative to understand the factors responsible for desertification to avoid the losses of agriculture minimize degradation of resources and increase their efficiency for sustainable development.